Sensory Evaluation of Yogurt-like Set and Yogurt-like Drink Produced by Indigenous Probiotic Strains for Market Test - Fathyah Hanum Pamungkaningtyas; Mariyatun Mariyatun; Rafli Zulfa Kamil; Ryan Haryo Setyawan; Pratama Nur Hasan; Devin Varian Wiryohanjoyo; Sri Nurfiani; Eni Zulaichah; Indyah S. Utami; Tyas Utami; Endang S. Rahayu (Indonesian Association of Food Technologists, 2018)
Lactic acid bacteria have been isolated from several Indonesian indigenous fermented foods and screened for the potential strains as probiotic candidates. The aim of this study was to evaluate sensory properties and respondents’ preference of yogurt-like set and yogurt-like drink with various Indonesian indigenous probiotic strains produced by dairy industry. Indigenous probiotics of Lactobacillus plantarum MUT-7 and Lactobacillus plantarum DAD-13 were used to produce yogurt-like set and yogurt-like drink. Family perception toward yogurt-like drink was performed in Yogyakarta involving 100 family members. The yogurt-like products were also compared to yogurt containing commercial Lactobacilus bulgaricus and Streptococus thermophilus or commercial yogurt produced by dairy company. Several sensory evaluation toward sensory properties and panelist’s preference were performed in different cities. The result showed that the indigenous probiotic L. plantarum DAD-13 and L. plantarum MUT-7 were potential to be used as a starter culture for the production of yogurt-like set and yogurt-like drink. The combination of indigenous probiotics and indigenous lactic acid bacteria S. thermophilus DAD-11 resulted in better sensory properties of yogurt set compared to combination of L. bulgaricus and S. thermophilus.